Implementasi Pengelolaan Berkelanjutan di Desa Wisata Budaya Lingga Kabupaten Karo - Riana Handayani Silalahi; Muhammad Khadry (Journal of Economic Education and Entrepreneurship Studies, 2024)
Amidst the rapid development of tourism in Indonesia, cultural village tourism has become increasingly prominent. These villages not only serve as attractive tourist destinations but also as centers for sustainable economic and cultural activities. This study investigates the implementation of sustainable management in Lingga Cultural Tourism Village, Karo Regency, North Sumatra, using the Global Sustainable Tourism Council (GSTC) framework. The village holds significant potential as a cultural tourism destination, especially with its traditional house "Siwaluh Jabu." However, challenges such as inadequate governance, limited human resources, and funding constraints hinder the sustainable management efforts in the village. Employing a qualitative method, primary data was gathered through interviews with local tourism managers, while secondary data was collected from relevant literature and sources. The study recommends strategic measures to enhance sustainable management implementation, including strengthening organizational structures, improving human resources, and increasing funding. It is hoped that the findings of this research will provide better insights into the implementation of sustainable management in Lingga Cultural Tourism Village and serve as a guide for stakeholders in decision-making and executing sustainable programs in the future.